Artificial Intelligence dan Implikasinya Terhadap Tujuan Pembelajaran Pendidikan Agama Kristen - Hasudungan Sidabutar; Horasman Perdemunta Munthe (Institut Agama Kristen Negeri Manado, 2022)
This article is motivated by the emergence of negative narratives on technological developments, including artificial intelligence technology. Artificial intelligence technology is often associated as a threat that will threaten the existence of human life. This mindset is certainly wrong and naive, because technology exists to facilitate human performance. This paper wants to explore fundamentally about the origins of artificial intelligence technology and how it is used for the practice of learning Christian religious education both in schools and in churches in the context of developing spirituality by using a descriptive qualitative approach based on literature. One of the goals to be achieved from this article is how artificial intelligence technology can be integrated as a learning medium to form student knowledge as a whole and integral. The final result of this article is expected to give awareness to teachers and Christian clergy that artificial intelligence technology is not a threat so that technology needs to be interpreted proportionally. The success of Christian religious education to shape spirituality that is practiced in schools and churches requires the involvement of teachers as educators, students and the use of technology, because human are integrated to the digital world